Pendistribusian Zakat Produktif Dalam Mensejahterakan Mustahik Atas Dana Zakat Yang Dikelola Baznas Provinsi Lampung - Yuniarti, Rosearistavia; Hilal, Syamsul; Fasa, Muhammad Iqbal (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Zakat is one of the obligations of Muslims as a form of social responsibility towards less fortunate members of the community. Zakat can be distributed in various forms, one of which is productive zakat, with the hope of providing benefits to the recipients (mustahik) as it is given in the form of business capital. Providing business capital to mustahik aims to empower them and lift them out of poverty. As in Baznas Lampung Province which managed to distribute 85% of zakat funds and given to 8 asnaf. One of the distributions is in the form of productive zakat where in March 2022 as many as 142 musthik were successfully empowered but on the one hand it is not comparable to the number of poor people in Lampung Province reaching 995,590. This is because the collection of zakat funds has not been maximized so that the distribution cannot be done to mustahik who have entrepreneurial skills but do not have capital due to being in the poverty line. The purpose of this research is to examine the distribution of productive zakat funds in improving the welfare of mustahik from the zakat funds managed by the Lampung Provincial Baznas. This research adopts a qualitative method with a sample of 10 people, consisting of 5 Baznas officials and 5 mustahik. Data collection was done through interviews with the research respondents or informants. The research results indicate that the distribution of productive zakat funds as business capital has been able to help the mustahik recipients in developing their businesses and enables them to use the profits to support their living needs, reducing their dependence on financial assistance from others.